Dracula - Brodey, Kenneth; De Conno, Gianni; Stoker, Bram, 1847-1912. ([Genoa, Italy] : Black Cat, 2009)
Adapts Bram Stoker's novel in which a bloodthirsty Transylvanian count wreaks havoc on the lives of an English businessman and his wife; and includes background on the work; vocabulary, grammar, and comprehension activities; and an audio CD.
"Step four, B2.1"--Front cover.
Based on: Dracula / Bram Stoker.
Adult.
Adult
Keywords: Readers; Reading materials